PENGARUH PEMAHAMAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PENGGUNA E-COMMERCE - Muhamad Lutfi; Intan Rahma Sari (LPPM STIE YKPN Yogyakarta, 2026)
This study aims to empirically examine the effect of tax understanding, tax socialization, and tax sanctions on taxpayer compliance among e-commerce users, particularly online business actors on the Tokopedia platform in Tangerang. This research employs a quantitative method with an associative approach. Primary data were collected through questionnaires using a Likert scale distributed to 100 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression along with classical assumption tests. The results indicate that partially, tax understanding and tax sanctions do not have a significant effect on taxpayer compliance, although both show a positive relationship. In contrast, tax socialization has a positive and significant effect and is the most dominant factor in improving compliance. Simultaneously, all variables influence taxpayer compliance. These findings highlight the importance of effective tax socialization strategies in increasing awareness and compliance in the e-commerce sector.